Análisis de la relación entre la oclusión traumática y el progreso de las recesiones gingivales: Revisión de la literatura durante el periodo 2014 - 2021 (2021)
The etiology of gingival recessions is associated with predisposing factors such as age, gender, anatomical factors, periodontal phenotype; and triggers such as trauma, inflammatory diseases, periodontitis. Objective: to establish the relationship that exists between traumatic occlusion and the progression of gingival recessions, to evaluate the different controversies that have arisen throughout different authors regarding the etiology of these alterations. A review of the literature on the subject was carried out. The search was done through some databases, applying inclusion and exclusion criteria